DIGITALIZATION MARKETING STRATEGY: CASE STUDY OF TERONG CREATIVE TOURISM VILLAGE, BELITUNG REGENCY - Nexen Alexandre Pinontoan; willy arafah; Hera Oktadiana; Rahmat Ingkadijaya (LPSDI Bina Patria, 2024)
This research examines the role of digitalization in sustainable tourism marketing in the Creative Tourism Village of Terong. The primary focus of this study is on how the use of digital technology enhances operational efficiency, expands market reach, and strengthens sustainable practices within the tourism context. The findings indicate that the adoption of digital technology, such as websites, mobile applications, and social media, plays a crucial role in promoting the Creative Tourism Village of Terong to a broader audience. Digitalization has enabled more effective communication with tourists, more efficient reservation management, and rapid and accurate information dissemination. Additionally, digital technology supports innovation in delivering engaging and interactive tourism content, thereby enhancing the tourist experience. In conclusion, the implementation of digital-based marketing strategies in the Creative Tourism Village of Terong has significantly contributed to achieving sustainable tourism development goals by leveraging technology to support economic, social, and environmental sustainability. Ongoing collaboration among all stakeholders and adaptation to technological changes are key to successfully marketing tourist destinations in the digital era.